A Modified Maxwell Garnett Model: Hysteresis in phase change materials. (October 2019) - Green, Nicolas G; Fang, Xu
Abstract: The dielectric properties of materials undergoing phase transitions are key to a number of modern and developing technologies, particularly when hysteresis is demonstrated in the response. This paper presents a modified Maxwell Garnett model for analysing electromagnetic hysteresis, using an asymmetric effective medium approximation to describe intermediate states in the phase change, establishing a link between effective medium and hysteresis analysis. The model has few input parameters and provides a phenomenological approach to describing electromagnetic hysteresis in various phase change materials.